Architecture and Nature in Japan: Nishizawa, Kuma e Fujimoto - Salvator-John Liotta (Agathón)
This paper defines the sense of nature for Japanese culture according to the interpretation of the philosopher Testuro Watsuji, provides an overview of the devices of traditional Japanese spatiality and shows through a critical analysis of various projects by Ryue Nishiwaza, Kengo Kuma and Suo Fujimoto as Japanese contemporary architecture has renewed its bond with nature. The results show a real interest in integrating nature into architectural design reflection and several strategies to do so.